The neuropathology of intimate partner violence - Dams-O’Connor, Kristen; Seifert, Alan C.; Crary, John F.; Delman, Bradley N.; Del Bigio, Marc R.; Kovacs, Gabor G.; Lee, Edward B.; Nolan, Amber L.; Pruyser, Ariel; Selmanovic, Enna; Stewart, William; Woodoff-Leith, Emma; et al. (Acta neuropathologica, 2023)
Lifelong brain health consequences of traumatic brain injury (TBI) include the risk of neurodegenerative disease. Up to one-third of women experience intimate partner violence (IPV) in their lifetime, often with TBI, yet remarkably little is known about the range of autopsy neuropathologies encountered in IPV. We report a prospectively accrued case series from a single institution, the New York City Office of Chief Medical Examiner, evaluated in partnership with the Brain Injury Research Center of Mount Sinai, using a multimodal protocol comprising clinical history review, ex vivo imaging in a small subset, and comprehensive neuropathological assessment by established consensus protocols. Fourteen brains were obtained over 2 years from women with documented IPV (aged 3rd–8th decade; median, 4th) and complex histories including prior TBI in 6, nonfatal strangulation in 4, cerebrovascular, neurological, and/or psychiatric conditions in 13, and epilepsy in 7. At autopsy, all had TBI stigmata (old and/or recent). In addition, white matter regions vulnerable to diffuse axonal injury showed perivascular and parenchymal iron deposition and microgliosis in some subjects. Six cases had evidence of cerebrovascular disease (lacunes and/or chronic infarcts). Regarding neurodegenerative disease pathologies, Alzheimer disease neuropathologic change was present in a single case (8th decade), with no chronic traumatic encephalopathy neuropathologic change (CTE-NC) identified in any. Findings from this initial series then prompted similar exploration in an expanded case series of 70 archival IPV cases (aged 2nd–9th decade; median, 4th) accrued from multiple international institutions. In this secondary case series, we again found evidence of vascular and white matter pathologies. However, only limited neurodegenerative proteinopathies were encountered in the oldest subjects, none meeting consensus criteria for CTE-NC. These observations from this descriptive exploratory study reinforce a need to consider broad co-morbid and neuropathological substrates contributing to brain health outcomes in the context of IPV, some of which may be potentially modifiable.